Comparison of Eye Movements over Faces in Photographic Positives and Negatives. (November 2013) - Luria, Saul M; Strauss, Mark S
Eye movements were recorded while subjects viewed ordinary portraits and photographic negatives of those portraits. Under both conditions they first studied sixteen portraits and then tried to decide which of forty-eight portraits they had just seen. They made more errors of recognition while viewing negatives, and their fixation patterns were significantly altered: there was a decrease in the percentage of fixations directed to the eyes, nose, and mouth, and an increase for such details as the ears, cheeks, chin, cap, and necktie. There was also a decrease in the ratio of fixations to the most fixated detail compared to the least fixated detail.